Tourist Activities in Multimodal Texts - Nekic, M. author. aut Link
XV, 227 p.
Keywords: The book is devoted to the analysis of promotional material of tourist activities on tourism websites, including walking, dining, and visiting natural and cultural heritage sights, as instances of multimodal texts through a case study of Croatian and Scottish tourism websites.